2022
DOI: 10.3390/ijms232012400
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed Genome-Scale Metabolic Model Characterizes Adaptive Metabolic Flux Changes in Peripheral Blood Mononuclear Cells in Severe COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) poses a mortal threat to human health. The elucidation of the relationship between peripheral immune cells and the development of inflammation is essential for revealing the pathogenic mechanism of COVID-19 and developing related antiviral drugs. The immune cell metabolism-targeting therapies exhibit a desirable anti-inflammatory effect in some treatment cases. In this study, based on differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…In line with the current study, other authors have reported similar findings concerning the 13 metabolites highlighted by the PCA' loadings. Tang et al [11], for example, reported a down-regulation of (3R,5S)-1-pyrroline-3-hydroxy-5carboxylate, a metabolite involved in the arginine and proline metabolism, among severe coronavirus disease 2019 (COVID-19) patients in comparison to healthy controls. (R)mevalonate down-regulation in deceased patients can be indicative of induced muscle weakness cause by prolonged hospitalization [12].…”
Section: Resultsmentioning
confidence: 99%
“…In line with the current study, other authors have reported similar findings concerning the 13 metabolites highlighted by the PCA' loadings. Tang et al [11], for example, reported a down-regulation of (3R,5S)-1-pyrroline-3-hydroxy-5carboxylate, a metabolite involved in the arginine and proline metabolism, among severe coronavirus disease 2019 (COVID-19) patients in comparison to healthy controls. (R)mevalonate down-regulation in deceased patients can be indicative of induced muscle weakness cause by prolonged hospitalization [12].…”
Section: Resultsmentioning
confidence: 99%